2020
DOI: 10.1108/jbim-06-2019-0309
|View full text |Cite
|
Sign up to set email alerts
|

Enabling roles of relationship governance mechanisms in the choice of inter-firm conflict resolution strategies

Abstract: Purpose This study aims to present an integrated framework and investigate the enabling roles of governance mechanisms (i.e. contract, interdependence, trust and communication) in the choice of effective conflict resolution strategies (CRS) that in turn facilitate buyer–supplier relationship (BSR) performance. Design/methodology/approach Using Web-survey, data are collected from 170 Finnish small- and medium-sized enterprises that have key relationships with suppliers. This study uses structural equation mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 70 publications
2
25
0
Order By: Relevance
“…Thus, managers should set up a platform for frequent communication to proactively exchange and update information relating to sustainability collaboration as well as provide prompt and relevant support to their firms' partners, as such solving miscommunication, sustainability goal misalignment, and failure to obtain resources from each other (Cai et al, 2017). Such an approach can not merely reduce potential conflicts but can even turn destructive conflicts into constructive ones (see Shahzad et al, 2020). As suggested by Vlaisavljevic et al (2016), firms and partners should agree on the use of a formal language to capture and codify the sustainability knowledge or sustainable codes of conduct such as utilising manuals, processes, and software.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Thus, managers should set up a platform for frequent communication to proactively exchange and update information relating to sustainability collaboration as well as provide prompt and relevant support to their firms' partners, as such solving miscommunication, sustainability goal misalignment, and failure to obtain resources from each other (Cai et al, 2017). Such an approach can not merely reduce potential conflicts but can even turn destructive conflicts into constructive ones (see Shahzad et al, 2020). As suggested by Vlaisavljevic et al (2016), firms and partners should agree on the use of a formal language to capture and codify the sustainability knowledge or sustainable codes of conduct such as utilising manuals, processes, and software.…”
Section: Managerial Implicationsmentioning
confidence: 99%
“…Doing so implies both a high degree of concern for oneself and for others involved in the cooperation. For example, Shahzad et al (2020) found that contract completeness between companies in a supply chain facilitates a more cooperative approach toward conflicts. Competition, again, is usually related to win-lose outcomes.…”
Section: Conflict Management In Coopetitionmentioning
confidence: 99%
“…Coopetition naturally involves a tension of two opposing logics, namely, cooperation and competition, which may lead to conflicts (Gnyawali et al, 2016;Le Roy and Fernandez, 2015;Sabri et al, 2020;Tidström, 2018). Conflicts in business relationships have attracted scholars from the traditional buyersupplier relationship viewpoint (Shahzad et al, 2020) and coopetitive relationship view (Tidström, 2018). Conflict management is one critical success factor in business relationships, as conflict outcomes may be functional or dysfunctional for the relationship (Eckert and Rinehart, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…When organizations seek and involve in external collaboration, inter-organizational trust, as a company's perceptions of reliability and integrity of relationship partners, plays a critical role not only in minimizing transaction cost and inter-firm conflicts but also maximizes the relationship commitment and overall performance [3], [4], [28]. Interorganizational trust implies that relationship partners do not act as opportunistically even when there are short-term goals and objectives.…”
Section: Impact On Inter-organizational Trustmentioning
confidence: 99%